The Impact of the Zoning System Policy on Students in Public Schools - Amelia Dewanti; Abd. Madjid (Journal in Teaching and Education Area, 2026)
The zoning system policy in New Student Admissions aims to provide equal access and improve the quality of education by prioritizing the distance between students’ homes and schools. This study investigates the effects of zoning policies on public secondary schools through a systematic literature review of 20 articles published between 2020 until 2024, using the PRISMA approach to ensure data accuracy. The findings show that zoning supports a more even distribution of students and better access to education. However, challenges persist, such as disparities in school quality, limited infrastructure, lack of public awareness, and fraudulent practices during the Admission of New Students. Furthermore, students who fail to enter their preferred schools often experience a decline in motivation. Collaboration between central and local governments is crucial to address these issues, especially by strengthening policies through adequate socialization, improving school quality, ensuring fair teacher distribution, and infrastructure development. When implemented effectively, the zoning system can serve as a strategic tool to promote justice and equity in education. Moreover, it fosters character building and environmental care, as students live closer to school and are more likely to maintain their learning environment, resulting in stronger community involvement and sustainable school development.